COMPARATIVE STUDY OF STATIC YOGA VERSUS PILATES IN THE TREATMENT OF CHRONIC LOW BACK PAIN. - JAIMINI B. PATEL,; Dr. SOUMIK BASU,; PROF. TUSHAR J. PALEKAR, (International Journal of Pharma and Bio Sciences, 2016)
Study was done to compare the effectiveness of static yoga versus pilates in the treatment of Chronic Low Back Pain. Subjects fulfilling inclusion, exclusion criteria were taken. Subjects were randomly allotted to the groups by lottery method. Initial evaluation of pain intensity was done using the Numerical Pain Rating Scale for pain, flexibility was measured by modified-modified schobers test, functional activity was recorded by ODI and core strength was measured using a pressure-biofeedback.Then participants were randomly allocated into 2 groups: Group A: Pilates Group B: Static Yoga. Group A were given Pilates as an intervention and group B were given Static Yoga as an intervention. It was given for 5 days/week for 4 weeks, 35 min /session. Outcomes were assessed post treatment. We concluded that Pilates is more effective in reducing pain and functional disability and increasing the range of motion and core-strength than Static Yoga.